Biodegradable microspheres for controlled drug/cell delivery and tissue engineering - Zhang, H (2012)
The synthetic biodegradable polymer poly(lactide-co-glycolide) (PLGA) has been widely explored as substrate biomaterials for controlled drug delivery and tissue engineering. ECM component heparin and bone mineral hydroxyapatite (HA) are attractive biomaterials which can functionalize the PLGA surface to improve cell cell response and to bring in the dual growth factor delivery, because heparin and HA both can improve cell responses and bind with various proteins. To combine the osteoconductivity of HA and the controlled drug release of PLGA microspheres, HA coated PLGA microspheres were developed by a 3 hour rapid HA precipitation on the PLGA microsphere surface. Effects of various fabrication parameters on microsphere and HA coating morphology were evaluated. This core-shell composite worked as a dual drug delivery device and demonstrated better cell cell response than PLGA microspheres without HA coating. Three different methods, including osmogen, extractable porogen and gas-foaming porogen, were evaluated to fabricate porous microspheres as injectable cell scaffolds in the tissue engineering. The gas-foaming method produced covered porous PLGA microspheres, on which a skin layer covered all the surface pores. The skin layer was hydrolysed by NaOH to control the surface porosity. The modified open porous microspheres have large continued surface areas between pores, which provided more continued areas for cell adhesion. The porous microspheres with controllable surface porosity and large surface continuity between pores could be novel injectable cell scaffolds. Heparin was immobilized on the open porous PLGA microspheres by a facile layer-by-layer assemble to combine the advantages of porous structure and the protein binding from heparin. The heparin-coated porous microspheres promoted cell adhesion, spreading, proliferation and osteogenic differentiation. Growth factor-like protein lactoferrin was immobilized on the heparin coated porous microspheres, which further enhanced MG-63 proliferation and osteogenic differentiation. The heparin-coated porous microspheres are promising multi-functional devices for controlled drug delivery and injectable cell delivery.